Status of Gould's Petrel Pterodroma leucoptera caledonica in New Caledonia: distribution, breeding biology, threats and conservation. (2nd October 2021) - Bretagnolle, Vincent; Renaudet, Ludovic; Villard, Pascal; Shirihai, Hadoram; Carlile, Nicholas; Priddel, David
ABSTRACT: Pterodroma leucoptera caledonica is a subspecies of Gould's Petrel endemic to New Caledonia. Its distribution, abundance and breeding biology are poorly known. Extensive surveys of New Caledonia between 1994 and 2014 located only two breeding colonies, and a further likely, but still unconfirmed; the total estimated size of the population could be of the order of 5000–7000 breeding pairs. Nesting burrows were situated either near streams or on slopes near ridges. The breeding phenology of caledonica was similar to that of the Australian leucoptera, but with a breeding calendar that lagged that of leucoptera by 2–4 weeks depending on year and breeding parameter. Breeding success was low, with evidence of a high level of predation of eggs, chicks and adults by rats, pigs and cats. Pigs also destroyed nesting burrows. Permanent bait stations installed to control rats at one colony appeared successful, but the control of pigs and cats is much more problematic. If, as expected, the level of predation observed at one colony extends across all breeding colonies, population decline is inevitable and extinction likely in the long term. With no populations of P. l. caledonica on predator-free offshore islands, translocation to such sites may be evaluated to safeguard this subspecies. In the meantime, we recommend that the global status of Gould's Petrel Pterodroma leucoptera be upgraded from Vulnerable to Endangered .